Polar power USA: full steam ahead into the Arctic - Paul, Michael (DEU, 2019)
The Arctic’s melting ice not only acts as an early warning system for the world’s climate, but also makes this region an indicator of change for international security policy. The Trump administration sees the Arctic primarily as an arena of competition between great powers. This could both benefit and harm the region. A greater engagement on the part of the USA would be welcome, but if it comes with an attempt to exclude other states, this would damage the high level of cooperation that has held sway in the Arctic thus far. US Arctic policy has become a variable that is dependent on great-power rivalry. The resulting polarisation of relations makes it difficult to find the necessary common solutions for coping with the changes caused by global warming. (author's abstract)